Analysis of Effectiveness and Challenges of Digital Zakat Management: Case Study on Shopee and Tokopedia Platform - Judijanto, Loso; Sudarmanto, Eko; Bakri, Asri Ady; Jasiah , Jasiah; Irwan, Muhammad (Westscience Press, 2024)
This research explores the Analysis of the Effectiveness and Challenges of Digital Zakat Management, focusing on the case study of Shopee and Tokopedia platforms through a quantitative approach. A diverse sample of 250 participants engaged in Zakat transactions provided insights into demographic profiles, usage patterns, and perceptions of digital Zakat features. Results indicate a broad appeal, with users spanning various age groups, professions, and geographic locations. Usage patterns varied, emphasizing the platforms' adaptability to users with different engagement frequencies. While users expressed high satisfaction (Mean Score: 4.1) and perceived efficiency in transaction speed (Mean Score: 4.2), challenges such as transparency concerns (Mean Score: 3.8) and technological barriers (30%) were identified. The study offers implications for platform optimization, emphasizing the importance of addressing challenges to enhance digital Zakat experiences.